A Juridical Analysis of the Authority of Traditional Health Practitioners in Medical Practice - T.Hermanto; U.Ismail (The Medical Journal of Hospital Management and Health Law, 2024)
Introduction: The integration of traditional medicine into the modern healthcare system creates a complex legal intersection regarding professional boundaries and patient safety. This study examines the legal authority of traditional health practitioners within the framework of conventional medical practice. Methods: This research employs a normative juridical method, analyzing statutory legislation, healthcare regulations, and legal doctrines governing health professionals. Results: The findings reveal that while statutory law formally recognizes traditional health practitioners, their scope of authority remains strictly segregated from conventional medical practices, creating operational ambiguities in collaborative clinical settings. Discussion: The literature underscores a persistent tension between protecting indigenous medical knowledge and enforcing standardized biomedical regulations. The discussion highlights that current legal frameworks fail to provide clear boundaries for integrative medicine, leaving practitioners vulnerable to liability and risking patient welfare due to overlapping responsibilities. Conclusions: In conclusion, the legal authority of traditional health practitioners is legally recognized but functionally restricted, necessitating explicit regulatory guidelines to harmonize traditional and modern medical practices safely. It is recommended that regulatory bodies establish comprehensive, joint-practice protocols and updated credentialing standards to mitigate legal risks.